Pentingnya Meningkatkan Pemahaman dalam Belajar TOEFL Bagi Siswa/i Kelas XII IPS SMAS Umum Sentosa - Sinaga, Reza Sanjaya; Situmeang, Vera Ningsi; Br Simanungkalit, Helen Renata; Zega, Kasih Lestari; Herman, Herman; Munthe, Melda Veby Ristella; Sherly, Sherly; Berlien, Richard (Indra Institute Research & Publication, 2023)
TOEFL (Test of English as a Foreign Language) has become one of the requirements for applying for jobs, continuing studies, and a standard for graduating students from college. The value of the TOEFL test has been recognized by 110 countries. The aim of this socialization activity is to increase the understanding of 20 students in class This socialization activity uses a lecture method in delivering material using PowerPoint, a question-and-answer session, and discussions regarding the extent to which they know about TOEFL and the obstacles they experience in understanding TOEFL. The location for this socialization activity is at Sentosa General High School, Jalan Benjamin BP. Mandoge, Huta Padang, District. Mandoge Sand City. And it will be held on November 1, 2023. In writing this article, the researchers used qualitative descriptive methods in collecting data. The result of this socialization activity is that students of class XII IPS SMAS Umum Sentosa can comprehend more about TOEFL with its benefit and some other important points to be prepared.